Perancangan Interior Fasilitas Restoran Mahameru di Surabaya - Danny Christopher Simon; Andereas Pandu Setiawan; Poppy Firtatwentyna Nilasari (Intra, 2017)
Food is one of the basic human needs and hence restaurants, such as Mahameru Restaurant in Surabaya, are designed to meet this need. This thesis project aims to redesign Mahameru restaurant with the concept of promoting the abundance and magnificence of Indonesian marine through the application of an aquarium as interior element and supplemented by visual information regarding the population and habitat of Indonesian fishery. The concept is inspired by sea and mountains (as depicted in the logo of Mahameru Restuarant), and hence the theme is named "water eruption" that articulates the mountain shape and the blue color, applied on the floors, walls, and ceilings of the restaurant. The interior adopts a coastal design style creating a warm beach atmosphere and dominated by blue color and natural wood material, thus supporting the concept that has been formulated and providing a more thematic atmosphere of Mahameru.